PENGARUH PEMBELAJARAN ONLINE (DARING) TERHADAP SIKAP BELAJAR DAN KETERAMPILAN BELAJAR SISWA SEKOLAH MENENGAH KEJURUAN JURUSAN AKUNTANSI DI KOTA TANGERANG - Sabur, Ambuy; Hidayati, Zulaikha; Ramdani, Heni Cahya (PELITA JURNAL PENELITIAN DAN KARYA ILMIAH, 2026)
The study aims to quantify comparisons of online learning and conventional learning based on the attitudes and learning skills of students. The study employs the ex post facto and comparison methods to draw a sample of two schools in the city of Tangerang, specifically SMK Nusantara 1 and SMK Lab Business School, involving 30 students from each school. The data gathering technique in the study employs questionnaires and literature reviews, while data analysis utilizes prerequisite testing and statistical analysis. The results illustrated the differences in learning attitudes and skills between online learning and conventional learning.